ASSESSING THE LEARNERS' SATISFACTION WITH TEACHING QUALITY AS A FACTOR OF UNIVERSITY COMPETITIVENESS RAISING - Nikolay N. Gagiev; Ekaterina A. Pirozhenko; Evgeniya V. Shubenkova (Вестник Российского экономического университета имени Г. В. Плеханова)
In today's market conditions, when the quality of education services become one of the most important factors for choosing the education institution it is crucial to assess the internal environment of the university, to find out the level of satisfaction of students as chief customers. The Russian Plekhanov University of Economics has adopted the Strategy of Education Quality Guarantee, on the basis of which the authors using their own methodology surveyed students in order to find the level of their satisfaction with teaching quality. The article drew the conclusions about the correlation between students' attendance and their results and between students' attendance and their marks. The criteria were identified under which lecturers got max and min grade on the basis of students' assessment at the Russian Plekhanov University of Economics.